Efektivitas Model Blended Learning dalam Meningkatkan Hasil Belajar di MTs Raadhiyatan Mardhiyyah Putri - Naharin , Siti Rowiyatun; Sopiah, Siti; Alfiyah, Siti Nur (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the effectiveness of the Blended Learning model in improving student learning outcomes at MTs Raadhiyatan Mardhiyyah Putri. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which involves planning, action, observation, and reflection in two cycles. The research subjects were eighth-grade students, with data collected through observation, tests, and interviews. The results indicate that the implementation of Blended Learning significantly enhances student learning outcomes, as reflected in the improvement of average scores across cycles. Additionally, this model increases students' active engagement, provides flexibility in accessing materials, and fosters more dynamic interaction between teachers and students. The combination of online and face-to-face learning also offers a more adaptive learning experience tailored to students' needs. Thus, Blended Learning can be an effective strategy to improve learning outcomes and instructional quality in madrasah education.